Aging studies on flame retardant treated lignocellulosic fibers. Issue 44 (2nd August 2016) - Molaba, Tshepiso Princess; Chapple, Steve; John, Maya Jacob
ABSTRACT: The study deals with chemical and flame retardant (FR) treatment of flax fabric. Sheets of flax fabric were subjected to chemical treatments using NaOH and silane coupling agents. A phosphate‐based flame retardant (DAP) was also applied to improve the flammability of the fabric. The effects of the chemical treatments and FR treatments on flax fabric were investigated using Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and vertical flame resistance test. Aging studies were carried out by exposing the samples in an environmental chamber at specified conditions for two weeks. The mechanical properties of the fabric, before and after environmental aging, were investigated. Flammability of flax fabric was improved after FR treatment. Thermal studies revealed a shift of decomposition temperature to lower temperatures and an increase in char residue after FR treatment. Despite treatment of the fabric with NaOH and silane, the tensile strength of FR‐treated flax fabric declined by more than 90% after aging for two weeks at 90 °C and 50% RH. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44175. Abstract :